2021
DOI: 10.3390/molecules26113313
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Economic Sustainability of Biochar Application on Corn Production in a Mediterranean Climate

Abstract: The effects of two types of biochar on corn production in the Mediterranean climate during the growing season were analyzed. The two types of biochar were obtained from pyrolysis of Pinus pinaster. B1 was fully pyrolyzed with 55.90% organic carbon, and B2 was medium pyrolyzed with 23.50% organic carbon. B1 and B2 were supplemented in the soil of 20 plots (1 m2) at a dose of 4 kg/m2. C1 and C2 (10 plots each) served as control plots. The plots were automatically irrigated and fertilizer was not applied. The B1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Different models were developed considering numerous factors that affect the costs and savings of amending with biochar. Aguirre et al followed a simplified model for calculating the benefit of improving corn production and for estimating the time required to cover the cost of biochar, considering the price of CO 2 fixation, to which they assigned a value of 30 EUR/t [33]. The price of CO 2 is constantly increasing after COP26, surpassing 90 EUR/t in February 2022 [47].…”
Section: Estimation Of Economic Viabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Different models were developed considering numerous factors that affect the costs and savings of amending with biochar. Aguirre et al followed a simplified model for calculating the benefit of improving corn production and for estimating the time required to cover the cost of biochar, considering the price of CO 2 fixation, to which they assigned a value of 30 EUR/t [33]. The price of CO 2 is constantly increasing after COP26, surpassing 90 EUR/t in February 2022 [47].…”
Section: Estimation Of Economic Viabilitymentioning
confidence: 99%
“…In recent years, many studies have assessed biochar effects on soil fertility and on the yield and quality of different horticultural crops, especially under water stress conditions. These studies have shown the efficacy of biochar in pumpkin [29], onion [30], pea [31], lettuce [32], corn [33], cucumber [34], sweet pepper [35], watermelon [36], and tomato [37] crops, among others. Conversely, other studies have not reported significant improvements in yield when supplying biochar [38], usually on soils fertile enough to meet all plant requirements, even under water stress conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a limiting factor to its widespread adoption is the high cost of production due to the use of pyrolytic furnaces, whose functioning depend on external energy supply, though pyrolysis units can be used to produce biochar and at the same time to create energy (Peters et al 2015;Kung and Mu 2019). Moreover, considering also the costs related to transport and distribution into the soil, Aguirre et al (2021) estimated that biochar application costs approximately 190 euros per ton.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the prerequisite for the largescale application of biochar was the economic feasibility of biochar application (Aguirre et al 2021), however, most of the current research still focuses on the environmental effects of biochar rather than the economic benefits (Owsianiak et al 2021). The main reason was the excessively high input costs of biochar and relatively slow benefits due to a large amount of biochar applied and the high price.…”
mentioning
confidence: 99%